Potentially Inappropriate Medications in Elderly Ambulatory Patients: A Comparative Study between a Primary Health Care Center and a Community Pharmacy - Chiapella, Luciana Carla (2018)
Objective: This study aims to compare, both qualitatively and quantitatively, the medication dispensed to elderly patients in a primary health care center (PHC) and a community pharmacy (CP) in Argentina and to identify the prescription of potentially inappropriate medications (PIMs). Methods: A cross-sectional observational study. Data were acquired from 886 prescriptions in the PHC and 2368 in the CP between February and April 2015. Dispensed medications were coded according to the Anatomical, Therapeutic, and Chemical (ATC) classification system. The frequency of prescriptions for each of them was determined. The number and monthly average of drugs dispensed were calculated for each patient. The use of PIMs was identified using Beers Criteria. Results: In both institutions, the means of medications dispensed per individual and month were similar: 3.69 ± 1.93 in the PHC and 3.46 ± 2.18 in the CP. Most of the medications corresponded to cardiovascular system agents. In the CP, 111 prescriptions (4.69%) dispensed to 51 patients (19.39%) were identified as PIMs. In the PHC, 72 prescriptions (8.13%) dispensed to 27 patients (28.42%) were identified as PIMs. In patients with major polymedication the possibility of consuming these drugs was 2.55 times higher in the CP and 2.60 times higher in the PHC. The percentage of PIM prescriptions was significantly higher in the PHC, although the percentage of patients receiving them did not differ significantly. Conclusions: The prevalence of PIMs found in this population is relevant enough to implement measures that address the problem in an integral way, to improve the quality of prescriptions and the health outcomes of patients.